Isolation and Identification of Flavonoid Compounds from Mangrove Leaves Burus (Bruguiera cylindrica (L.) Blume) - Tonel Barus; Jonathan Sihombing (Talenta Publisher, 2024)
Flavonoid compounds have been successfully isolated from the Mangrove leave burus (Bruguiera cylindrica (L.) Blume) through a series of extraction processes. The maceration procedure, which involved soaking the material to be extracted in methanol solvent to allow the desired chemicals to dissolve gradually, was used for the first extraction. Following the addition of ethyl acetate, the extract was concentrated once more. This ethyl acetate extract is subsequently dissolved in methanol and partitioned with n-hexane. The obtained methanol layer was evaporated until dry, then analyzed using thin layer chromatography (TLC), with silica gel as the stationary phase and chloroform as the mobile phase. The composition of the chloroform:methanol eluent used varied (90:10, 80:20, and 70:30 v/v), and the pure amorphous solid compound with an orange-yellow color was successfully obtained using a 70:30 v/v eluent, weighing 16.3 mg and having an Rf value of 0.73. Compound identification was carried out using UV-Visible, FT-IR, and Â¹H-NMR. Spectroscopic data indicate that the extracted compound belongs to the flavonol group.